INDUSTRI PENGOLAHAN SALAK & PEMBERDAYAAN EKONOMI MASYARAKAT STUDI ANALISA SWOT DI TAPANULI SELATAN - fasya fasya (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2017)
The object of this study was to find out how the prospect of salacca processing industry of UD.Salacca is in building economy of society depends on Islam perspective. The method of the study was qualitatif approach which the techniques of collecting the data were interview and documentation. The analysis of the data was SWOT analysis which is to find out the strengths, the weaknesses, the opportunities, and the threats of the industry. Based on result of the interview held to the interviewees then the researcher finds out some strengths such as strategic location, wide market share, MUI halal label and satisfied profits while the weaknesses are not sophisticated technology and expired of the products. Then, the business opportunities are support of the government and achievement of foreign market while the threat which is faced is new business competitors so that it can be concluded that salacca processing industry of UD. Salacca is deserved and prospective to be developed.